Perencanaan Sistem Informasi Web Pemesanan Toko Niko Elektrik - Mendita, Gaizka; Sutrisno, Tri; Lewenusa, Irvan (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The advancement of information technology has had a significant impact on the business sector, especially in the growth of e-commerce, which provides opportunities for SMEs to increase sales and expand their market reach. Niko Electric Store, founded in 2003 in Jakarta, is one of the SMEs that have adapted to this trend by transitioning to an e-commerce platform to remain competitive. This research focuses on the development of the Niko Electric Store e-commerce website using the System Development Life Cycle (SDLC) methodology, which includes the planning, analysis, design, development, and testing phases. The website is designed to facilitate customers in accessing products such as LED lights, cables, and power outlets, and offers features such as online shopping, a secure payment system, and responsive customer service. Additionally, promotional campaigns and attractive offers are also integrated to enhance user engagement. This development aims to expand market reach, improve operational efficiency, and simplify customer transactions. By utilizing a structured SDLC approach, this project ensures the quality of the website and user satisfaction. This digital transformation is expected to help Niko Electric Store remain competitive, better meet customer needs, and drive sustainable business growth in the digital era.